The analysis of causes of divorce by wives - Nurhasanah, Nurhasanah (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
This study aimed to find out the background of the life of women until the marital process, the factors causing wives to sue their husband for divorce, and the overview of women’s life who sued their husband for divorce. The research uses descriptive qualitative method and for collecting data were doing interviews. The subjects of this research were ten people. The results showed that most of their propensities to divorce were because: (1) the husband did severe persecution that was harmful to the wife; (2) the husband left the wife for 2 (two) consecutive years without wife's permission and without any legitimate reason; (3) the occurrence of dispute and the quarrel between the husband and wife as well as there was no hope of living in harmony anymore in the household; (4) the husband committed adultery (cheating). Based on the results from the study, divorced women feel free from her husband's bad behavior.